Brain imaging technologies to study infant behavior and development - Esposito, Gianluca (2020)
Brain imaging techniques have developed in neuroscience to investigate neural mechanisms underlying early human development. Some methodologies measure electrical activity in different brain regions (Electroencephalography – EEG) or magnetic fields produced by electrical currents arising in the brain (Magnetoenchephalography – MEG). Others measure the level of oxygenation of the blood in different brain areas using near infrared light (Near Infrared Spectroscopy - NIRS) or magnetic fields (Magnetic Resonance Imaging - MRI). These techniques were initially developed to study human adults and not, until recently, utilized to study infant behavior and development. They are all rapidly gaining adherents and application, even as their adaptation to study infants is challenging and debatable and clear conventions about their use not settled.